2008
DOI: 10.1371/journal.pone.0003435
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Intima-Media Thickness, Carotid Plaque and Coronary Heart Disease and Stroke in Chinese

Abstract: BackgroundOur aim was to prospectively investigate the association between carotid artery intima-media thickness (IMT) as well as carotid plaque and incidence of coronary heart disease (CHD) and stroke in Chinese, among whom data are limited.Methods and FindingsWe conducted a community-based cohort study composed of 2190 participants free of cardiovascular disease at baseline in one community. During a median 10.5-year follow up, we documented 68 new cases of coronary heart disease and 94 cases of stroke. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 56 publications
(66 reference statements)
2
58
2
1
Order By: Relevance
“…The normal human serum visfatin level is 15.8 ± 16.7 ng/mL. (16) CCA-IMT was determined using standard procedures, (17) with…”
Section: Methodsmentioning
confidence: 99%
“…The normal human serum visfatin level is 15.8 ± 16.7 ng/mL. (16) CCA-IMT was determined using standard procedures, (17) with…”
Section: Methodsmentioning
confidence: 99%
“…18,19,26 Participants with a baseline history of stroke events (nϭ89) were excluded from this study. Incident stroke cases were ascertained according to the following criteria: a sudden neurological symptom of vascular origin that lasted Ͼ24 hours with supporting evidence from the image study; fatal stroke cases were included.…”
Section: Follow-up Strategy and Outcome Ascertainmentmentioning
confidence: 99%
“…In a communitybased cohort study in a Chinese population a significant association was found between carotid IMT and incidence of CHD and stroke in Chinese adults, but neither the AUC for CHD nor that for stroke significantly improved after IMT addition to the TRF model (103). Also the NRI was not significantly increased, although a modest but significant increase in the IDI was evident (103). In the MultiEthnic Study of Atherosclerosis (MESA), evaluating incident CVD events (CHD, stroke, and fatal CVD) over a maximum of 5.3 years of follow-up, not only was coronary artery calcium (CAC) associated more strongly than carotid IMT with the risk of incident CVD, but a ROC analysis also suggested that CAC score was a better predictor of incident CVD than was IMT, with AUC of 0.81 versus 0.78, respectively, after adjustment for TRFs (102).…”
Section: Intima -Media Thicknessmentioning
confidence: 89%
“…In a communitybased cohort study in a Chinese population a significant association was found between carotid IMT and incidence of CHD and stroke in Chinese adults, but neither the AUC for CHD nor that for stroke significantly improved after IMT addition to the TRF model (103). Also the NRI was not significantly increased, although a modest but significant increase in the IDI was evident (103).…”
Section: Intima -Media Thicknessmentioning
confidence: 90%
See 1 more Smart Citation